Rancangan Pembelajaran Berkarakteristik Pembelajaran Inovatif Abad 21 Ada Materi Procedure Text dengan Model Pembelajaran Problem Based Learning di Smp Negeri 1 Pangkah - Herry Kristanto (Cakrawala: Jurnal Pendidikan, 2022)
In order to improve quality human resources, the field of education has a very urgent role. The learning process guided by a scientific approach involves observation activities to formulate hypotheses or collect data. In the learning process students need to be accustomed to solving problems, finding something useful for themselves and struggling with ideas. Therefore, in learning students must be actively involved and become the center of learning activities or student-centered learning will be active if the teacher masters in making learning designs that are characterized by the 21st century. This learning design needs to be supported by six main things, namely 1) Student collaboration and teachers, 2) HOTS orientation, 3) Integrating information and communication technology, 4) Oriented on learning skills and developing 21st century skills, 5) Developing literacy skills, and 6) Strengthening character education or PPK. Teachers also need to develop appropriate learning models as guidelines in the teaching and learning process so that students learn to be more active, creative, innovative, and joyful. Learning models that are in accordance with Curriculum 13 are Project Based Learning, Discovery Learning, and Problem Based Learning. The learning model must be implemented according to the steps or syntax.